The Effect of Online Game Addiction and Learning Concentration on Social Science Students’ Learning Outcomes in Eight Grage of Private Junior High School Kartika 1-4 Pematang Siantar - Devi Irene M Rumapea; Susy Alestriani Sibagariang; Benjamin Albert Simamora (International Journal of Humanities and Education Development (IJHED), 2022)
This study aims to determine the effect of online game addiction and learning concentration on social studies learning outcomes at Kartika 1-4 Private Junior High School Pematang Siantar. The research method used ex post facto. Data collection techniques using a questionnaire. Respondents were 86 students. The data analysis technique used multiple linear regression. The results showed: 1) in the calculation of online games students of Kartika 1-4 Private Junior High School Pematang Siantar obtained a significant level of 0.241 > 0.05 and Fcount (1,394) > Ftable (3.11) so Ho was accepted, thus there was no significant effect between the games. on the learning outcomes of eighth grade students of Kartika 1-4 Private Junior High School Pematang Siantar. 2) In calculating the learning concentration of Kartika Private Junior High School students 1-4 Pematang Siantar, the significance level was 0.027 < 0.05 and Fcount (5.010) > Ftable (3.11). So, Ho is rejected, thus the effect that occurs is significant between learning concentration on learning outcomes. 3) In calculating online game addiction and learning concentration of Kartika Private Junior High School students 1-4 Pematang Siantar, the significance level was 0.021 < 0.05 and Fcount (4.034) > Ftable (3.11). Thus, there is a significant effect between online game addiction and learning concentration on learning outcomes